IN VITRO PLANT REGENERATION FROM CHRYSANTHEMUM CALLUS INDUCED BY GAMMA IRRADIATION AND ISSR GENETIC ANALYSIS - Maulida, Dr., Desi; Taisa, Rianida; Erfa, Lisa; Wahyu Prajaka, Nanang; Febria, Dilla; Hamiranti, Rahmadyah; Mubarok, Syariful (Departement of Agrotechnology, Agriculture Faculty, Universitas Lampung, 2025)
Conventional breeding methods of chrysanthemum plants face several challenges to overcome, and physical mutagens such as gamma rays have proven effective in creating chrysanthemum mutants. As an important tool in flower germplasm innovation and variety improvement, gamma rays have greater penetrating power compared to other breeding methods. This research aims to determine the effect of various doses of gamma irradiation on chrysanthemum callus growth, plant regeneration, and morphology due to induction and to determine the existence of genetic variations using ISSR markers. The experiment consisted of four stages, namely, chrysanthemum callus explants were irradiated at doses of 0, 10, 20, and 30 Gray using gamma rays to induce mutations and observe the effect on callus growth. The irradiation results were planted in BA media 0.5, 1.5, and 3.0 mg L-1 to observe shoot growth. Next, the shoots were planted in rooting media containing NAA with and without activated charcoal (AC) for plant regeneration and amplification of chrysanthemum genomic DNA. The results showed that a lower radiation dose (10 Gray) had a positive influence on all growth parameters, while 30 Gray caused a significant reduction in plant height and number of leaves. NAA 1 mg L-1 AC 2 mg L-1 media gave the best results in supporting the growth of chrysanthemum plants at various levels of radiation exposure. Analysis using ISSR markers confirmed the presence of genetic variation in irradiated plants.